Effect of Clove Powder Syzygium aromaticum Supplementation on Growth and Health Status of Cantang Grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) in Floating Net Cage - Sukenda Sukenda; Widanarni Widanarni; Dinamella Wahjuningrum; Munti Yuhana; Mia Setiawati; Inem Ode (Jurnal Perikanan Universitas Gadjah Mada, 2023)
Cantang grouper is a hybrid grouper which is one of the main grouper species cultivated in Indonesia. This study aimed to evaluate the growth and health status of cantang grouper in floating net cages supplemented with clove powder. This study used a completely randomized design with three treatments, each with three replications. Two levels of clove powder dose used were 10 and 15 g kg-1 and one treatment without clove powder dose (control). Feed treatment using the repelletting method. Parameters observed were growth, survival rate, levels of malondialdehyde and superoxide dismutase enzyme, blood parameters, phagocity activity, total bacterial count (TBC) and total vibrio count (TVC). The results showed that the treatment of clove powder supplementation in cantang grouper feed for 30 days was able to increase the growth, survival rate, activity of the enzyme superoxide dismutase (SOD), and differential leukocyte (lymphocyte). The application of clove powder in the feed did not significantly affect the total erythrocytes, leukocytes, hematocrit, phagocytic activity, total bacterial count (TBC) and total vibrio count (TVC) of hybrid grouper in floating net cages. The conclusion of this study, administration of clove powder at a dose of 15 g kg-1 feed was able to significantly increased growth, differential leukocyte (lymphocyte), and survival rate of cantang grouper in floating net cages.